Kualitas Pengalaman Wisatawan dan Citra Destinasi Terhadap Minat Berkunjung Kembali Melalui Kepuasan Wisatawan Sebagai Variabel Intervening Museum Kartini Rembang - Cahyati, Ratih Nur; Welsa, Henny; Fadhilah, Muinah (Jurnal Ilmiah Global Education, 2025)
This study aims to determine the quality of tourist experiences and destination image on the intention to revisit through tourist satisfaction as an intervening variable. The population of this study is all tourists who have visited the Kartini Museum in Rembang, with a sample collection technique using purposive sampling. The number of samples used was 140 respondents. Data analysis was conducted using the partial least squares (PLS) SEM method based on variance, utilizing the SmartPLS software version 3.2.9. The results of the study indicate that tourist experience quality partially has a positive effect on the intention to revisit, destination image partially has a positive effect on the intention to revisit, tourist experience quality partially has a positive effect on visitor satisfaction, destination image partially has a positive effect on visitor satisfaction, and visitor satisfaction partially has a positive effect on the intention to revisit. Visitor satisfaction was found to mediate the relationship between tourist experience quality and the intention to revisit, while tourist satisfaction was found to mediate the relationship between destination image and the intention to revisit.